The Southeast Asian connection : trade and polities in the Eurasian world economy, 500 BC-AD 500 - Chew, Sing C. (Berghahn, 2018)
"The contribution of Southeast Asia to the world economy (during the late prehistoric and early historic periods) has not received much attention. It has often been viewed as a region of peripheral entrepôts, especially in the early centuries of the current era. Recent archaeological evidence revealed the existence of established and productive polities in Southeast Asia in the early parts of the historic period and earlier. This book recalibrates these interactions of Southeast Asia with other parts of the world economy, and gives the region its due instead of treating it as little more than of marginal interest"--